Integrated Saving Matrix - Branch And Bound Method to Optimize Sugar Product’s Distribution Route - Devanda, Ryan Rafli; Pulansari, Farida (Spektrum Industri, 2022)
The problem in product delivery is always being late and the company has not utilized the capacity of distribution transportation equipment to the fullest. This study aims to determine the shortest distribution route and minimize distribution costs using the Saving Matrix -Branch and Bound methods. In this study, the Saving Matrix method use to produce the shortest route distance, while the Branch and Bound method is applied to optimize a route distance. The results found that the Saving Matrix method followed by the Branch and Bound method reduced routes from the previous seven routes to five routes. Meanwhile, The proposed distribution model shortens the route of 23.6% compared to the current, and cost savings is 23%. To conclude, the model of distribution distance affects the costs savings and optimum route